Fostering Reflective Thinking in Physical Education Teachers: An Action Research Study Promoting Paralympic Values and Inclusive Practices - Theofanis Kaloudis; Konstantinos Georgiadis; Antonios K. Travlos; Yannis Theodorakis (Education Sciences, 2025)
This study explores the development of reflective thinking among Physical Education Teachers (PETs) through a professional development program grounded in Paralympic values and inclusive education. Employing a qualitative action research design, the study involved seven PETs teaching in Greek primary schools. The intervention lasted ten weeks and comprised 20 Physical Education lessons, during which data were collected via semi-structured interviews, reflective journals, and non-participatory observation. The findings indicate a progressive shift in the teachers’ reflective thinking—from Technical Reflection to Practical and Critical Reflection—as defined in van Manen’s theoretical model. Most participants initially demonstrated a practical orientation but gradually developed a critical stance, incorporating values such as fairness, inclusion, and respect for diversity into their pedagogical thinking. Furthermore, the results revealed increased student sensitivity toward inclusive practices and a more democratic classroom climate. These findings suggest that targeted professional development programs can foster deeper reflective engagement and promote inclusive practices within Physical Education. This study highlights the potential of Paralympic values as meaningful educational content and reinforces the role of Physical Education as a catalyst for social inclusion and teacher professional growth.